Ma'anil Hadith Study on Controversy of Women's Voices as Aurat - Zahrotun Nisa; Abdul Wasik (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the study of the hadith maanil on the hadith controversy that women's voices are aurat. This research is a qualitative type that applies literature study with multi-method and ethnographic approach. The results of this study include a discussion of the concept of women's voices, the ma'anil hadith of women's voices, and the opinions of scholars regarding women's voices. This study concludes that the hadith narrated by Imam Bukhari has a higher position than the hadith narrated by Imam Tirmidhi, so that the hadith of Imam Bukhari is superior in its validity. The majority of the scholars also stated that women's voices are not part of the genitals on the condition that they are safe from slander. This research recommends that this simple research can be completed with research from various perspectives